Leptin at the intersection of neuroendocrinology and metabolism: current evidence and therapeutic perspectives. - Dalamaga, Maria; Chou, Sharon H; Shields, Kelsey; Papageorgiou, Panagiotis; Polyzos, Stergios A; Mantzoros, Christos S (Cell Metab, 2013)
Since its discovery as an adipocyte-secreted hormone, leptin has been found to impact food intake, energy homeostasis, and metabolism through its effects on the central nervous system and peripheral organs. Recent research indicates that leptin may also be involved in cognition, immune function, and bone metabolism. These findings place leptin at the intersection of neuroendocrinology and metabolism, and possibly immune function, and render it an appealing therapeutic target for several niche areas of unmet clinical need. Current evidence regarding classic and emerging roles of leptin as well as the pros and cons of its potential clinical use are summarized herein.
Keywords: Bone and Bones; Carbohydrate metabolism; Central nervous system; Cognition; Energy Metabolism; homeostasis; Humans; Immune System; Leptin; Neurosecretory Systems